STRATEGI PENANGGULANGAN KEBAKARAN PADA LAHAN GAMBUT DENGAN MENGGUNAKAN PENDEKATAN EKO-TEKNOLOGI PADA MASYARAKAT PETANI DI DESA RIMBO PANJANG KECAMATAN TAMBANG KABUPATEN KAMPAR PROVINSI RIAU - Saktioto Saktioto; Defrianto Defrianto; Riad Syech; Syahril Syahril; Joko Risanto (Komunikasi Fisika Indonesia, 2018)
People who care about the environment always reject the use of peat land for large-scale plantation areas, because this can cause an increase in carbon gas and can even cause damage to peat land in Rimbo Panjang Village, Tambang District, Kampar Regency. that there was an event of a land fire which almost hit the residential area in Rimbo Panjang village, Kec. Kampar District Mine on February 24, 2015. That there are complaints from the community in Rimbo Panjang village, Kec. Kampar Regency Mine about environmental conditions or smog. The implementation of Eco-Technology can protect the environment of peatlands to maintain sustainability and avoid fire from peatlands and regulate groundwater management on peatlands.